PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MELAKUKAN OPERASI HITUNG CAMPURAN DI KELAS IV SD - Amiga, Halimatussaqdiah; Ahmad, Syafri; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The Purpose of this research was to estabiish the effect of Discovery Learning toward students’ achievement in the operation mixed count at the fourth of Elementary School. The method of this researah was Quasi Experiment by Non Equivalent control group design. The sample in this research was the students’ at the fourth grade of SDN 11 Pudung and the students’ at the fourth grade of SDN 18 Pudung. The instrumentation was used the test. Hypothesis testing in this research was used the formula of t-tes and N-Gain. Based on the resuit of this research was shown that the mean class of Discovery Learning were 80 and control class were 78. Based on the calculated of t-test were 2,40146109 was highere that t-tabel were 1,86385. It can conciuded that there was the effect of Discovery Learning toward students achievement. Keyword    : Students’ Mathematics Achievement, Discovery Learning, The                            Operation Mixed count